PERSEPSI GURU TENTANG REWARD AND PUNISHMENT DAN IMPLEMENTASINYA DALAM PEMBELAJARAN DI MAN II MODEL MEDAN - Candra Wijaya; M. Luthfie Ramadhani; Edi Jatmiko (Nazhruna: Jurnal Pendidikan Islam, 2020)
In everyday life, we often encounter children with diverse characters. There are children who are easy to foster and some who are difficult to foster, some are keen to learn and some are very lazy to learn, some of them learn to progress and some of them learn just to avoid punishment. Actually the bad qualities that arise in the children above are not born and their nature. These traits arise due to the lack of early warnings from parents and educators. So it is a big mistake if we underestimate the small mistakes made by children. In fact, there are no educators who want punishment to be used in education unless forced to. Gifts or compliments are far more important than punishment. In the world of education, this method is called the reward and punishment methods. With this method, it is hoped that students can be motivated to do progressive deeds. This study aims to describe and analyze teacher perceptions about reward and punishment and its implementation in learning in MAN 2 Medan Model.